From the experience of organizing artistic and productive activities of older preschool children by means of distance education in the conditions of quarantine measures for the spread of COVID-19 - Iryna Trubavina; Victoria Vorozhbit-Gorbatyuk; Maryna Shtefan; Kateryna Kalina; Oksana Dzhus (Academy of Cognitive and Natural Sciences, 2021)
The relevance of the article relates to the need for continuing preschool education under quarantine conditions to prevent the spread of COVID-19 by means of distance technologies and preparation of children for STEAM education. Artistic and productive activities are considered to be the resource of STEAM education. The aim of the article is to substantiate educational opportunities of distance education programs for undertaking artistic and productive activities of older preschool children on quarantine. Research methods: theoretical analysis, surveys, generalization of experience, analysis of children's products, parental feedback. The scientific basis of the study is a set of approaches of different levels. Scientific novelty of the research is two-fold. The possibility of organizing artistic and productive activities of older preschool children by means of remote technologies in terms of preparing parents to interact with educators and organizational, technical, informational assistance to children. The features of the organization of such education in Ukraine under conditions of introducing quarantine measures are revealed. Practical significance is viewed through development and approbation of the content of classes on artistic and productive activities, integrated with the fundamentals of mathematics. There have been developed the questionnaires on digital competence for educators and digital literacy for parents.